Allama al-Amiri ( died : 893) and his approach to quoting from the books of al-Sihah in his book Bahjat al-Mahafeel wa Bighat al-Amthal in summarizing biographies, miracles and merits (Journal of the College of Basic Education, 2022)
Scholars, in the old and present have been studying the biography and merits of the Prophet, and they relied in their books on many resources from which they took this blessed biography, especially the people of hadith who transmitted authentic hadiths from the narrators. Of those narrators was the scholar “ Muhammad al-Amiri, nicknamed Abu Zakaria” who died in the year ( died : 893 AH), in his book (Bahjat al-Mahafil Wa Bighyat al-Amthal in summarizing biographies, miracles and merits) and his method in his book is that he quoted information from many sources and many resources, and among these resources are the honorable hadiths from the books of Al-Sihah. For The importance of this book I wanted to show its resources from Al-Sihah books.